West : Fire : Archive - Dunkle, Iris Jamahl (Book collections on Project MUSE., 2021)
"West : Fire : Archive is a poetry collection that challenges preconceived, androcentric ideas about biography, autobiography, and history fueled by the western myth of progress presented in Frederick Jackson Turner's "Frontier thesis." The first section focuses on mending the erasure of the life of Charmian Kittredge London, the wife of the famous author Jack London, a woman who broke gender norms, traveled the world, and wrote about it. The second section examines the act of autobiography (or what defines the author). In it, Dunkle writes through the complex grief of losing her mother and her community when it is devastated by wildfires and reflects on how these disasters echo the one that brought her family to California, the Dust Bowl. The third section questions the authenticity of the definition of recorded history as it relates to the American West"--